Effects of Instagram on visitors' attachment to revitalised historic city centres in Georgetown, Penang, Malaysia and Chinatown, Singapore - Ertan, Tugce (2022)
Modern cities are experiencing the challenging consequences of rapid urbanization, such as decay, problems concerning safety, aesthetics, loss of urban identity, social life, and physical deterioration in the built environment. Historic city centres, which are the core elements of cities’ identities, are particularly faced with abandonment and decline, resulting in the danger of cultural heritage and identity loss. Therefore, revitalising historic city centres and converting them to healthy living environments has become an urgent issue. Despite the fact that most regeneration and renovation practices concentrate on creating more human-friendly environments, they mostly focus on physical enhancements and less on the psychological element of attachment formed between people and places. Another modern world fact is the undeniable role of social media in our daily lives. This also affects how users experience places and form attachments to place, since it has become integrated as a digital layer to how people experience the world today. Even though place attachment provides continuity over time and a sense of belonging in historically significant places, social media usage is ever-increasing and there is not much research on the use and effect of popular social media tools on rehabilitated urban spaces and how they may work as a place-attachment tool for such rehabilitation projects. The objective of this thesis is to explore the effects of Instagram on visitors’ place attachment to revitalized historic city centres. For this purpose, a case study approach was chosen employing a mixed methodology. The quantitative method sampled 421 respondents from two cases, Georgetown historic city centre in Penang, Malaysia, and Chinatown historic city centre in Singapore. Data were collected through questionnaire surveys as the main method and supported by a netnography method, which was conducted online. The questionnaires measured how Instagram played a role on place attachment formation through destination image, place involvement, and collective memory, and the results were analysed by conducting a mediator analysis. The netnography method collected the Instagram posts of visitors and then analysed the data by content analysis within a hermeneutic approach. Using a mixed methodology from multiple case studies allowed the researcher to gain rich data and make comparisons. After the individual analysis of the cases, a cross-case analysis was done to see if the initial hypotheses were supported. The last step was to discuss the findings and respond to the research questions. The findings revealed that Instagram usage has a significant positive effect on destination image, place involvement, collective memory, and place attachment. Furthermore, it was seen that destination image and collective memory played a mediating role between Instagram usage and place attachment. Although place involvement was not found to be a predictor for place attachment or a mediator between Instagram usage and place attachment quantitatively, the netnographic study interpreted this from the Instagram posts. The study suggests that destination image and collective memory plays the most vital role in the effect of Instagram usage on place attachment to historic city centres. Furthermore, enhancing visitors’ place attachment to historic city centres will support stronger place identity that could turn decayed historic city centres into frequently used and embraced responsive environments. The findings provide a wholesome view of how Instagram usage shapes the place attachment process before, during and after visiting a place. The central message of this study is that integrating Instagram usage into historic city centre revitalisation will generate and enhance place attachment and will help strengthen the place identity of cities.